Exploring Pancasila Student Profile in "Jembatan Pensil" film - Pitaloka, Nadia Sekar Ayu (Beyond Words, 2024)
The purpose of the research is to explore the six dimensions of the Pancasila Student Profile contained in the film entitled “Jembatan Pensil” by Hasto Broto. The method of the research is discourse analysis, which refers to converting spoken language into written language, transcribing data, and presenting the results. Then, the results show that this film is appropriate and suitable to be used as learning media for the audience, especially for young learners. Furthermore, it is expected that the Pancasila Student Profiles can be applied in students' everyday lives both at school and outside school. In this study, researchers conclude that the Jembatan Pensil film is a medium that can be taken into consideration as a learning medium in the form of literature as another means of implementing the Pancasila Student Profile while utilizing technological developments and becoming an increasingly varied learning strategy.